Influence of Graphitic Carbon Nitride (g-C3N4) on Mechanical and Thermal Properties of Pineapple Leaf Fibre Reinforced Polyester Resin Composites - Md. Nurunnabi; Shah Alimuzzaman Belal; Borhan Uddin; Ruhul Amin Khan (Textile & Leather Review, 2024)
Natural fibres, which are recyclable and environment friendly, are becoming more popular than synthetic fibres which are commonly utilized in manufacturing composite materials. Scientists have drawn attention to natural fibres because of their availability, cost-effectiveness, and biodegradability. Recently, it has been popular practice to include natural fibres in composite materials for industrial uses. The research deals with the fabrication of pineapple leaf fibre (PALF) reinforced polyester composites prepared from PALF used as reinforcement with 6 wt% (weight fraction). Synthesized graphitic carbon nitride (g-C3N4) was used as filler in different weight fractions such as 0.25, 0.50, 0.75, and 1.00 % to improve the mechanical and thermal properties of the fabricated composites. Graphitic carbon nitride (g-C3N4) was synthesized by one-step heating methods from scrap melamine. Fourier-transform infrared spectroscopy was utilized to characterize g-C3N4 and ensured successful synthesis. According to the results, the composite with 0.75 wt% of g-C3N4 has a higher modulus and tensile strength. Tensile strength increases as g-C3N4 weight percentages rise, demonstrating the filler's beneficial effects. The appearance of cracks in PALF/polyester composites with g-C3N4 was captured by scanning electron microscopy, which points to the morphological changes arising after tensile testing. With the addition of g-C3N4 in several weight percentages, the thermal resistance and water repellency of composites were significantly improved. Overall, this research reveals the effect of filler weight percentage on the mechanical, thermal, and morphological properties of PALF/polyester composite. The investigation concludes that a defined weight proportion of g-C3N4 with PALF and polyester resin produces composite materials with acceptable mechanical properties suitable for engineering applications where composites are best.